GEOMECHANIC AND CRITICALLY STRESSED FRACTURES ANALYSIS FOR MAXIMUM WATER INJECTION PRESSURE IN DURI FORMATION, FIELD B, CENTRAL SUMATERA BASIN, RIAU. - DARAJAT (NIM: 22014301), YADZIL
Field B is located approximately160 km northwest from Pekanbaru which is included into the area Contractors Cooperation (PSC) PT. Chevron Pacific Indonesia. Field B has 11 reservoirs within Telisa, Duri, and Bekasap Formation, with Duri Formation was the focus at the beginning of the operation of this field. Continuous production leads to a significant drop in the pore pressure of the reservoirs in Duri Formation and a declination of the oil production in this field, therefore the reservoirs of Duri Formation need a water injection to solve these problems. Knowledge of the stress in the subsurface is crucial to understand the tectonic regime that works in Field B at this time. Geomechanics models can be used to comprehend the stress condition on fractures and fault at subsurface. The maximum pressure of water injection in the reservoir is depend on the stress condition on faults and fractures. Geomechanics analysis was perfomed on five wells using log data and direct measurement data. SHmax and Shmin were also calculated using stress polygon. Based on the geomechanical model, the tectonic regime is a normal fault regime (Sv>SHmax>Shmin) with the orientation of Shmax and Shmin are are NE-SW and NW-SE respectively. Vertical stress gradient has a value range from 0,87 – 0,88 psi/ft, SHmax: 0,79 – 0,81 psi/ft, dan Shmin: 0,75 - 0,76 psi/ft. Based on the critical stress analysis, the faults and fractures at Duri Formation are not in a critical condition. The maximum pressure of water injection for Duri Formation is 0,71 psi/ft.